Importations de produits laitiers et politique d'importation au Mali; effets sur le secteur laitier dans la region de Bamako - Massow, V.H. von (CIPEA, 1986)
Discusses the economic relationship among supply, demand and imports of dairy products in the Bamako area focussing on the influence of government policy on dairy imports. Includes a brief description of production, consumption & trade patterns; the policy measures affecting dairy imports; factors influencing the development of consumption, production & import; and a calculation of economic effects of dairy imports & related policies. Also discusses the role of the dairy plant ULB (Union Laitiere de Bamako) focussing on ULB's price and marketing policy and its economic and financial situation.